Pemanfaatan Ekstrak Enzim Jamur Humicola sp. Sebagai Biotermitisida Utilization of Humicola sp. Enzyme Extract as Biotermiticide - Ikhsan Guswenrivo; Titik Kartika; Didi Tarmadi; Sulaeman Yusuf (Masyarakat Peneliti Kayu Indonesia, 2008)
Fungal spore can be used for biotermiticide, since it has high pathogen properties and environmentally safe. However, the utilization of enzyme extract of fungi can be developed as an alternative way to minimize the impact caused by the spore when they are used as biotermiticide. This research was done to observe the ability of enzyme extract from Humicola sp. The fungus was inoculated in sorghum substrate and grown in it by adding either colloidal chitin or without colloidal chitin to the media as variation of the medium composition. Extraction was done after 3, 5, and 7 days of incubation time. Extract was done by using cold sterilized water (40C). Then the extract kept it at low temperature (40C). Bioassay of extract enzyme was done by spraying and baiting method. Result of the bioassay showed, Humicola sp enzyme extract was grown from medium adding with colloidal chitin and incubation for 7 days give highest mortality of termite increase to 100% after 14th day observation.